Fresh properties and compressive strength of MPC-based materials with blended mineral admixtures. (December 2022) - Feng, Hu; Nie, Shuang; Guo, Aofei; Lv, Lijun; Chu, Liusheng; Yu, Jiahuan
Abstract: To explore the feasibility of using blended mineral admixtures to improve the performance of magnesium phosphate cement (MPC) composites, fly ash (FA) + ground granulated blast furnace slag (GGBS) and fly ash (FA) + silica fume (SF) were used to partially replace the MPC, respectively, in this study. Their effects on the setting time and flowability of MPC paste and the compressive strength of MPC mortar (MPCM) were investigated through setting test, flowability test, and compressive test. The test results showed that the blended FA and GGBS adversely affected the setting time of MPC paste but slightly improved the flowability of MPC paste and the compressive strength of MPCM if an appropriate content was used. And the blended FA and SF adversely affected both the setting time and flowability of MPC paste. However, compared to the MPCM without any mineral admixture or with SF (FA) alone, the 25 % FA+ 5 % SF, 32.5 % FA+ 7.5 % SF, and 35 % FA+ 5 % SF could further enhance the compressive strength of MPCM. In addition, the XRD and SEM tests showed that the blended FA and GGBS mostly resulted in loose microstructure of MPCM. However, an appropriate content of blended FA and SF could lead to the formation of a dense microstructure, and a new magnesia-silica gel substance (MgSiO3 ) was generated, which improved the compactness and compressive strength of MPCM.